2011
DOI: 10.1073/pnas.1113035108
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin neurons mediate reflex ovulation in the musk shrew ( Suncus murinus )

Abstract: The present study investigated whether kisspeptin-G protein-coupled receptor 54 (GPR54) signaling plays a role in mediating mating-induced ovulation in the musk shrew (Suncus murinus), a reflex ovulator. For this purpose, we cloned suncus Kiss1 and Gpr54 cDNA from the hypothalamus and found that suncus kisspeptin (sKp) consists of 29 amino acid residues (sKp-29). Injection of exogenous sKp-29 mimicked the mating stimulus to induce follicular maturation and ovulation. Administration of several kisspeptins and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 37 publications
1
73
1
1
Order By: Relevance
“…Clinically difficult egg collection was Conversely, peripheral administration of kisspeptin triggers egg maturation in female rats primed with gonadotropins (28). In addition, exogenous administration of kisspeptin induces ovulation in the musk shrew (26), rats (28), and sheep (29). In keeping with this, human studies demonstrate that kisspeptin stimulates LH release most potently during the preovulatory phase of the menstrual cycle (i.e., the time of the cycle just prior to ovulation) in females with regular, normal menstrual cycles (18,21,30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinically difficult egg collection was Conversely, peripheral administration of kisspeptin triggers egg maturation in female rats primed with gonadotropins (28). In addition, exogenous administration of kisspeptin induces ovulation in the musk shrew (26), rats (28), and sheep (29). In keeping with this, human studies demonstrate that kisspeptin stimulates LH release most potently during the preovulatory phase of the menstrual cycle (i.e., the time of the cycle just prior to ovulation) in females with regular, normal menstrual cycles (18,21,30).…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to consider the safety of kisspeptin in IVF treatment. Kisspeptin is a naturally occurring peptide hormone that plays a physiological role in triggering ovulation (25)(26)(27)(28)(29). Reassuringly, circulating levels of kisspeptin-54 rise dramatically, up to 7,000-fold, during normal human pregnancy and remain elevated for the duration of a normal nine-month pregnancy (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, subsequent studies have shown that kisspeptin stimulates GnRH secretion via GPR54 on GnRH neurons [48][49][50]. The amino acid sequence of kisspeptin, especially the C-terminal 10-amino acid sequence, is well conserved in most mammals [51][52][53][54][55][56][57]. Hypothalamic kisspeptin neurons are mainly located in the anterior and posterior nuclei; i.e., the anteroventral periventricular nucleus (AVPV)/preoptic area (POA) and arcuate nucleus (ARC) [55,56,[58][59][60][61][62][63][64].…”
Section: Physiological Roles Of Kisspeptin and Gnih/rfrp-3mentioning
confidence: 99%
“…The amino acid sequence of kisspeptin, especially the C-terminal 10-amino acid sequence, is well conserved in most mammals [51][52][53][54][55][56][57]. Hypothalamic kisspeptin neurons are mainly located in the anterior and posterior nuclei; i.e., the anteroventral periventricular nucleus (AVPV)/preoptic area (POA) and arcuate nucleus (ARC) [55,56,[58][59][60][61][62][63][64]. Kiss1 mRNA expression in the AVPV/POA is increased in the afternoon during proestrus and is also upregulated by the administration of estrogen, whereas Kiss1 mRNA expression in the ARC is decreased by the administration of estrogen [61,63,[65][66][67].…”
Section: Physiological Roles Of Kisspeptin and Gnih/rfrp-3mentioning
confidence: 99%